Rice Production and Nitrogen Use Efficiency by Diverse Forms of Fertilization in Rice-Based Crop Rotation Systems - Woojin Kim; Moon-Sub Lee; Jwakyung Sung (Agronomy)
The rising demand for climate change mitigation has brought attention to agricultural systems focused on carbon farming and reducing emissions. Composting food wastes and livestock manure not only mitigates environmental concerns but also boosts soil fertility and crop yields as an alternative fertilizer. In this experiment, we investigated the effects of different fertilizer types (chemical and organic waste compost) and crop rotations (rice–fallow, rice–Italian ryegrass, and rice–potato) on rice production, nitrogen use efficiency, and soil carbon stocks. In this experiment, soil carbon and nitrogen retention were more influenced by compost nutrient levels than by crop rotation types. Overall, as the nitrogen levels increased, the rice yields improved with both chemical and organic waste fertilizers. Among the crop rotations, the rice–Italian ryegrass rotation showed a higher nitrogen use efficiency. Optimal fertility levels, balancing nitrogen use efficiency, yield, and soil carbon were observed between 523 and 582 kg N ha−1 when combined with specific crop rotations. Moreover, soil total carbon and soil total nitrogen varied among crop rotation systems. Our results indicate that organic waste compost can be a potential alternative to chemical fertilizers, while crop rotations offer a viable approach for maximizing the environmental benefits.